Upaya Orang Tua dalam Pencegahan Kekerasan Seksual terhadap Anak - Mega Ade Nugrahmi; Chyka Febria; Kartika Mariyona; Pagdya Haninda Nusantri Rusdi; Amelya Permata Sari (Universitas Batanghari Jambi, 2023)
Cases of sexual violence that occur against children are caused by the child's ignorance of the actions taken by the perpetrator to carry out the action which is not in accordance with existing norms in society. One of the efforts to prevent sexual violence is carried out jointly and is a shared responsibility, it cannot be done by parents alone but must be able to collaborate with the government, community institutions, schools, professional staff who have knowledge of child development. This research aims to describe and explore the obstacles to parents' efforts to prevent sexual violence against children in Nagari Tanjuang Bungo, Limapuluh Kota Regency. This research is qualitative in nature, informants were selected using a purportive sampling technique with 3 informants. In-depth interview techniques use recording equipment and interview guides as well as taking notes in the field. Data analysis uses the Miles and Huberman principles. The obstacles faced by parents in preventing sexual violence are due to knowledge and work factors which mean that parents do not spend much time with their children at home. It is hoped that the local government will provide more information to parents regarding the impact of sexual violence so that this deviant behavior does not have a negative impact on both children and parents.